Knowledge Synergy Among Lecturers in Public Universities in Rivers State - Chinyere, Amini-Philips; Adaeze, Nwanosike, Victoria (European Scientific Journal, ESJ, 2018)
Knowledge synergy refers to a continuous knowledge creation process which fuses people with diverse capabilities from diverse places, departments, organizations, institutions and facilities to share, exchange, integrate, combine and transfer their knowledge as they work together to achieve the same goal rather than individuals working independently. Knowledge synergy is pivotal in the achievement of university goals because it kindles productivity. The researchers examined knowledge synergy among lecturers in public universities in Rivers State. Three research questions were answered and three corresponding hypotheses were tested in this study. The study adopted a descriptive research design. The population of the study comprised all the 2330 lecturers in the three public universities in Rivers State, Nigeria. The sample size was 746 lecturers. The stratified randomsampling technique using 32% of the population gave the sample size. The researchers made instrument titled Knowledge Synergy among Lecturers in Public Universities Questionnaire (KSLPUQ), was used for data collection. The instrument contained 43 items that addressed the three research questions. Face and content validities were ensured. The reliabi1ity coefficient of 0.92 was obtained with the help of Cronbach alpha. Descriptive statistics: mean and standard deviation was used to answer the three research questions while the z-test statistics was used to test the three null hypotheses at 0.05 level of significance. It was found out among others that lecturers practice knowledge synergy to a very great extent in the three public universities in Rivers State. Again, the types of knowledge synergy practised are academic conferences, workshops, seminars, joint authorship, general staff meetings and one-on-one discussions. It was recommended among others that; heads of department should always pair senior and junior lecturers in the discharge of teaching and non-teaching activities to enrich their knowledge level. Universities’ Vice Chancellors, Deans and Provost should also be able to make knowledge synergy a prerequisite for promotion in the university system.